Challenges experienced in the dental care of persons with special needs: a qualitative study among health professionals and caregivers - Ramaa Balkaran; Talia Esnard; Maureen Perry; Jorma I. Virtanen (BMC, 2022)
Abstract Background This study aimed to explore the challenges experienced in dental health care by professionals and caregivers of persons with special needs in Trinidad and Tobago. This research presented results from the first qualitative study which gained insight into the service component of dental care for people with special needs in this country. Methods This qualitative study was conducted between March and June 2021. Recruitment of participants used both purposive and snowball sampling. A semi-structured interview schedule was used in the interviews of dentists, (a dental assistant), physicians and caregivers of people with special needs. Narrative inquiry was used in data analysis. The transcripts were individually coded and a follow-up peer debriefing session to cross reference responses and increase the validity of the analysis was performed. Results Barriers related to the provision of dental care included readiness of health care professionals, the level of specialized care and the resources required for patient treatment. Caregivers encountered barriers such as cost and lack of accessible dental care for persons with special needs. Possible solutions were education of key stakeholders, policy intervention, advocacy and prevention strategies. Conclusions Caregivers and allied health care professions experience multiple barriers when treating patients with special needs. Study participants indicated a need change in the provision and access of dental services for people with special needs. Education of healthcare professionals, improved social policies and health promotion is warranted.